Enhancing Employee Wellbeing in the Digital Era: The Influence of Digital Literacy and Affective Leadership in Addressing Digital Burnout - Putra, Ramdani Bayu; Fitri, Hasmaynelis (Economics, Business, Accounting & Society Review, 2025)
Digital burnout has emerged as a critical global workplace challenge, particularly in digitally intensive environments where constant connectivity strains employee wellbeing. This study examines how digital literacy and affective leadership shape digital burnout and employee wellbeing within the Department of Communication and Informatics of Padang City. It also assessed the mediating effect of burnout on employee wellbeing. An explanatory, cross-sectional survey design was employed, and data were analyzed using variance-based structural equation modeling. The measurement model meets conventional standards for convergent validity, construct reliability, and discriminant validity, with a noted conceptual proximity between digital literacy and wellbeing that warrants attention. Structural findings indicate that affective leadership is negatively related to digital burnout, whereas digital literacy both reduces burnout and strongly enhances employee wellbeing. By contrast, the direct paths from affective leadership to wellbeing, from burnout to wellbeing, and the indirect routes through burnout did not show significant effects. Overall, digital literacy emerges as a central lever for improving wellbeing and curbing technology-related exhaustion in digitally intensive settings, while leadership contributes chiefly through preventive influences on fatigue. Practical implications include tiered digital upskilling, responsive technical support, and digital wellbeing policies aligned with empathic leadership. Future work should refine indicators, explore contextual moderators, and adopt longitudinal designs to strengthen causal inferences.